Jewish-Christian Interpretation of the Pentateuch in the Pseudo-Clementine Homilies - Carlson, Donald H. (Minneapolis : Fortress Press, 2013)
"The pseudo-Clementine writings are one of the most intriguing and valuable sources for early Jewish Christianity. They offer a second- or third-century polemic against the form of Christianity that eventually won out, the Gentile-majority, law-free Christianity that took Paul as its champion. Carlson's interest here is in the highly unusual theory expressed in the Homilies that the Pentateuch is saturated with "false pericopes," and that the teaching of Jesus, the "true prophet," is the criterion for establishing what the Pentateuch really means"--Page 4 of cover
Abbreviations -- Overview of Previous Scholarship -- The Rejection of Allegorism -- The Theory of the False Pericopes -- The True Prophet's Teaching as an Exegetical Criterion -- Oral Tradition as an Exegetical Criterion -- The Harmony Criterion -- Summary and Conclusion -- Bibliography -- Index of Names and Subjects -- Index of Greek Terms -- Index of Ancient Sources
Includes bibliographical references (pages 221-239) and indexes
Text in English; some quotations in Greek
Keywords: Xavier University (Cincinnati, Ohio) -- Faculty -- Publishing; Homilies (Pseudo-Clementine); Bible. -- Criticism, interpretation, etc. -- History -- Early church, ca. 30-600; Christian literature, Early -- Greek authors -- History and criticism